Pengaruh Media Pembelajaran Geoenzo Terhadap Kemampuan Pemecahan Masalah Matematis - Ishak, Suryadi (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
This research is an experimental study that aims to determine the effect of GeoEnzo learning media on students' mathematical problem solving abilities on the subject of quadrilaterals and triangles. The population in this study were all students of class VII SMP Negeri 1 Polewali totaling 223 people and the samples were students of class VII C totaling 31 people and VII D totaling 31 people. The research instrument used a problem-solving ability test, student activity sheets, and the implementation of student learning. The collected data were analyzed using descriptive statistical analysis and inferential statistics. From the results of statistical analysis, the average value of the pretest in the experimental class was 56.19 and the control class was 63.29. While the posttest average value in the experimental class is 87.93 and the control class is 64.32. Judging from the activities of students obtained an average percentage of 83.56%. The results of the calculation of the t test for posttest data obtained a value of 11.774. As for the value of 1.670 which means that is 11.774> 1.670. From the results of descriptive statistical analysis and inferential statistics, it was concluded that the GeoEnzo learning media had an effect on the mathematical problem solving abilities of seventh grade students of SMP Negeri 1 Polewali.